Arbitrase Solusi Alternatif dalam Penyelesaian Sengketa - Irnawati I; Adenis Satriawan (Media Hukum Indonesia (MHI), 2026)
Arbitration is one of the alternative dispute resolution mechanisms regulated under Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution in Indonesia. This study aims to analyze the advantages and challenges of arbitration in resolving business disputes in the Republic of Indonesia. The findings indicate that arbitration offers several significant advantages, including a faster dispute resolution process, more predictable and manageable costs, confidentiality, and decisions that are final and legally binding. However, the implementation of arbitration continues to face several challenges, such as limited understanding of arbitration procedures among business actors, difficulties in enforcing arbitral awards, and arbitration costs that, in certain cases, may be higher than litigation in court. To optimize the role of arbitration, greater public awareness and education, reforms in the enforcement of arbitral awards, enhancement of arbitrators' professional capacity, and simplification of regulations concerning arbitration costs are necessary. Through these measures, arbitration can serve as an effective and reliable mechanism for resolving business disputes in Indonesia.